Further expanding the mutational spectrum of brain abnormalities, neurodegeneration, and dysosteosclerosis: A rare disorder with neurologic regression and skeletal features. Issue 6 (22nd March 2021) - Kındış, Erdem; Simsek‐Kiper, Pelin Özlem; Koşukcu, Can; Taşkıran, Ekim Z.; Göçmen, Rahşan; Utine, Eda; Haliloğlu, Göknur; Boduroğlu, Koray; Alikaşifoğlu, Mehmet
Abstract: Colony stimulating factor 1 receptor ( CSF1R, MIM# 164770) encodes a tyrosine‐kinase receptor playing an important role in development of osteoclasts and microglia. Heterozygous CSF1R variants have been known to cause hereditary diffuse leukoencephalopathy with spheroids (HDLS, MIM# 221820), an adult‐onset leukoencephalopathy characterized by loss of motor functions and cognitive decline. Recently, a new phenotype characterized by brain abnormalities, neurodegeneration, and dysosteosclerosis (BANDDOS) with biallelic CSF1R pathogenic variants in the etiology has been described. BANDDOS differs from HDLS by early‐onset neurodegenerative changes with additional structural brain abnormalities and skeletal findings resembling dysosteosclerosis (DOS). Described skeletal findings of the disease are highly variable ranging from absence of a skeletal phenotype and milder Pyle disease‐like to osteopetrosis and DOS. To date, only a few patients carrying biallelic CSF1R variants have been reported. In this clinical report, we describe three siblings with variable skeletal findings along with neurological symptoms ranging from mild to severe in whom exome sequencing revealed a novel homozygous splice site variant in canonical splice donor site of intron 21 adjacent to an exon, which encoding part of kinase domain of CSF1R along with a review of the literature.